ABUNDANCE OF EPIPHYTIC DIATOM IN RhizophoraCOVERED AND NOT COVERED BY PLASTIC IN PECINTA ALAM BAHARI DUMAI - Lukman Harun; Sofyan Husein Siregar; Irvina Nurrachmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractDiatoms are unicellular organisms from the Bacillariophiceae class, can be found as planktonic diatoms and benthic diatoms. This research was carried out in July 2018, in Pecinta Alam Bahari (PAB), Dumai Barat. This study aims to find out the type, distribution, and abundance of epiphytic diatoms in Rhizophora.The method use in this study was the survey method.Point sampling was determined by purposive sampling, each point sampling consists of 3 sub-sampling (trees). there are 9 types of epiphytic diatoms in mangrove Rhizophora sp. on roots covered and were not covered by plastic, it wasCoscinodiscus sp., Cyclotella sp., Isthmia sp., Melosira sp., Leptocylindrus sp., Stepanopixis sp., Gyrosigma sp., Navicula sp., and Synedra sp. The lowest total abundance of diatoms in the roots covered by plastic and those not covered by plastic is at the sampling point I, which is 689.28 ind/cm2and 1,132.40 ind/cm2. The highest diatom abundance in roots covered and not covered by plastic were at the sampling point III, which is 1,230.87 ind/cm2 and 1,477.04 ind/cm2. Based on the results of t-test obtained a significant value of< 0.05 i. e. 0,032 indicating the abundance of ephipythic diatoms was significantly different in the roots covered and not covered by plastic.Keywords : Diatom, Abundance, covered and not covered by plastic